(untitled) (Journal of Current and Advance Medical Research, 2023)
Background: The on examination and radiological findings of tubercular and malignant pleural fluid may vary among patients with exudative pleural effusion. Objective: The purpose of the present study was to assess the on examination and radiological findings of tubercular and malignant pleural fluid collected from patients presented with exudative pleural effusion. Methodology: This cross-sectional study was carried out at medicine indoor department of Sylhet MAG Osmani Medical College Hospital, Sylhet, Bangladesh from October 2009 to March 2010. Patients who were admitted with pleural effusion were selected as the study population. Pleural fluid was collected and laboratory tests were performed in the Department of Laboratory Medicine of the Hospital. The clinical features and haematological findings of tubercular and malignant pleural fluid were assessed. Results: A total of 50 cases were selected consecutively in the study. Among 30 tuberculars pleural effusion, chest movement and expansion decreased in 26 cases. However, in 12 malignant pleural effusion cases, most of the patients’ chest movement and expansion were found diminished which was in 9 cases. Radiological findings showed that more than half (54.0%) of the patients had right sided pleural effusion. Conclusion: In conclusion chest movement and expansion as well as vocal resonance are decreased in both tubercular and malignant pleural effusion patients with absent of breath sound. Journal of Current and Advance Medical Research, July 2022;9(2):74-78